ROLES AND FUNCTIONS OF ARTIFICIAL GALLERY FOR MODERN ART ARTIFICIAL GROWN IN SURABAYA AT 2000S - Mohamad Arifin; Fabiola Dharmawanti; Djuli Djatiprambudi (Proceeding of International Conference on Art, Language, and Culture, 2017)
Art gallery is one of fine arts infrastructures. Art galleries have important roles and functions in the modern arts development. It also distributes the artwork that is created by artists as the producer and presented to the public as the consumer. Surabaya is one of the big cities that became part of the modern art development. Moreover, the development of modern art is located in urban areas. It is also influenced by infrastructure and superstructure in synergy to form the social arts field. On the decade of 2000 in Surabaya, there are many new galleries that both established by individuals and private institutions. The appearance of the gallery certainly brings impact and influence on the art activities in Surabaya. It can be seen from the increase of exhibition activities that is organized by the gallery. The art gallery as a public space has the obligation to engage in artistic activity and foster the public's appreciation of cultural and commercial values of art.